(untitled) (International journal of artificial intelligence, 2025)
This article covers the theoretical foundations of wellness fitness aerobics exercises, methodological approaches and their positive impact on human health. Fitness aerobics as a popular form of physical activity offers exercise complexes adapted for different age groups. The article analyzes the principles of Organization of aerobics training, the criteria for their selection, the health-improving effect that they show on the cardiovascular, respiratory, muscular and nervous system. Safety, loading and technical issues are also covered in the practical application of exercises, and some exercise complexes are presented as an example.